Physics and optimization of plasma startup in the RFP. (9th April 2015) - Mao, W.; Chapman, B.E.; Ding, W.X.; Lin, L.; Almagri, A.F.; Anderson, J.K.; Den Hartog, D.J.; Duff, J.; Ko, J.; Kumar, S.T.A.; Morton, L.; Munaretto, S.; et al.
Abstract: In the tokamak and reversed-field pinch (RFP), inductively driven toroidal plasma current provides the confining poloidal magnetic field and ohmic heating power, but the magnitude and/or duration of this current is limited by the available flux swing in the poloidal field transformer. A portion of this flux is consumed during startup as the current is initiated and ramped to its final target value, and considerable effort has been devoted to understanding startup and minimizing the amount of flux consumed. Flux consumption can be reduced during startup in the RFP by increasing the toroidal magnetic field, B ti, applied to initiate the discharge, but the underlying physics is not yet entirely understood. Toward increasing this understanding, we have for the first time in the RFP employed advanced, non-invasive diagnostics on the Madison Symmetric Torus to measure the evolution of current, magnetic field, and kinetic profiles during startup. Flux consumption during startup is dominantly inductive, but we find that the inductive flux consumption drops as B ti increases. The resistive consumption of flux, while relatively small, apparently increases with B ti due to a smaller electron temperature. However, the ion temperature increases with B ti, exceeding the electron temperature and thus reflecting non-collisional heating. Magnetic fluctuations also increase with B ti, corresponding primarily to low- n modes that emerge sequentially as the safety factor profile evolves from tokamak-like to that of the RFP.